History of the discovery of a master locus producing piRNAs: the flamenco/COM locus in Drosophila melanogaster - Coline, Goriaux; Théron, Emmanuelle; Brasset, Emilie; Vaury, Chantal (Frontiers in Genetics, 2014)
The discovery of transposable elements (TEs) in the 1950s by B. McClintock implied the existence of cellular regulatory systems controlling TE activity. The discovery of flam an heterochromatic locus from Drosophila melanogaster and its ability to survey several TEs such as gypsy, ZAM and Idefix contributed to peer deeply into the mechanisms of the genetic and epigenetic regulation of TEs. flam was the first cluster producing small RNAs to be discovered long before RNAi pathways were identified in 1998. As a result of the detailed genetic analyses performed by certain laboratories and of the sophisticated genetic tools they developed, this locus has played a major role in our understanding of piRNA mediated TE repression in animals. Here we review the first discovery of this locus and retrace decades of studies that led to our current understanding of the relationship between genomes and their TE targets.